Correlation Between Postvaccination Anti-Spike Antibody Titers and Protection Against Breakthrough Severe Acute Respiratory Syndrome Coronavirus 2 Infection: A Population-Based Longitudinal Study. (30th July 2022) - Vivaldi, Giulia; Jolliffe, David A; Faustini, Sian; Shields, Adrian M; Holt, Hayley; Perdek, Natalia; Talaei, Mohammad; Tydeman, Florence; Chambers, Emma S; Cai, Weigang; Li, Wenhao; Gibbons, Joseph M; et al.
Abstract: In this population-based cohort of 7538 adults, combined immunoglobulin (Ig) G, IgA, and IgM (IgG/A/M) anti-spike titers measured after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination were predictive of protection against breakthrough SARS-CoV-2 infection. Discrimination was significantly improved by adjustment for factors influencing risk of SARS-CoV-2 exposure, including household overcrowding, public transport use, and visits to indoor public places. Anti-spike IgG/A/M titers showed positive correlation with neutralizing antibody titers ( r s = 0.80 [95% confidence interval, .72–.86]; P < .001) and S peptide–stimulated interferon-γ concentrations ( r s = 0.31 [.13–.47]; P < .001). Abstract : Postvaccination anti-spike immunoglobulin (Ig) G, IgA, and IgM titers are modestly predictive of breakthrough severe acute respiratory syndrome coronavirus 2 infection but show poor correlation with interferon γ responses. Their limited predictive value for protection may therefore stem from their inability to reflect protective vaccine-induced cellular responses.